Transport Properties of Gramicidin A Ion Channel in a Free-Standing Lipid Bilayer Filled With Oil Inclusions - Tawfik, Harvey; Puza, Sevde; Seemann, Ralf; Fleury, Jean-Baptiste (Frontiers in Cell and Developmental Biology, 2020)
Ion channels are key proteins in mammalian cell membranes. They have a central role in the physiology of excitable cells such as neurons, muscle, and heart cells. They also play a crucial role in kidney physiology. The gramicidin ion channel is one of the most studied ion channels, in particular it was intensively employed to investigate the lipid–protein interactions in model cell membranes. For example, even though the sequence of gramicidin is extremely hydrophobic, its motion is impaired in membrane bilayer, i.e., it does not rapidly flip to the other membrane leaflet, and low channel activity were observed when gramicidin is added asymmetrically to only one leaflet of a model cell membrane. In this article, we study the transport properties of gramicidin channel in a heterogeneous model membrane. Using microfluidics, we are forming freestanding bilayers as model cell membranes including heterogeneous domains that are created by oil inclusions. The presence of oil inclusions is then demonstrated by measuring the bilayer capacity via a patch-clamp amplifier and fluorescent confocal inspection. Based on electrophysiological and optical measurements Gramicidin A (gA) ion channels are dispersed into the buffer phases on both side of the formed lipid bilayer and insert spontaneously into the bilayer upon formation. The presence of functional Gramicidin A is then demonstrated by measuring conductivity signals. Based on electrophysiological and optical measurements, we explore the consequence of the presence of these oil inclusions on the functionality of incorporated gA ion channels. For low oil concentration, we measure a decrease of gA transport properties due to the reduction of the bilayer tension. For large oil concentration, we measure a saturation of gA transport properties due to an increase of the bilayer thickness.